(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
ABSTRACT This article aims to demonstrate the State’s ineffectiveness in implementing public policies aimed at children and adolescents victims of intra-family violence. Although few studies demonstrate that there was a considerable reduction in the number of complaints compared to the years 2020 to 2019. However, there is no reason for celebration, as what is effective, in times of pandemic of Covid-19, is the underreporting of cases of violence. This is mainly due to isolation and social distancing made the juvenile public even more vulnerable, as confined to the aggressor, they do not even have the means to denounce, directly or indirectly, the violence suffered. The research is classified as deductive, descriptive and bibliographic. It appears that the state’s omission is clear, with regard to the implementation of public policies aimed at the effective guardianship of children and adolescents who are victims of intra-family violence, requiring the accountability of those responsible and the action of organized society to make the infant public effective in times of pandemic. Keywords: Intrafamily Violence. Under-notification. Public policy. Pandemic.